Music in Health and Diseases - Agrawal, Amit; Sutar, Roshan; Jallapally, Anvesh (IntechOpen, 2022)
It is well recognized that music is a unique and cost-effective solution for the rehabilitation of patients with cognitive deficits. However, music can also be used as a non-invasive and non-pharmacological intervention modality not only for the management of various disease conditions but also for maintaining good health overall. Music-based therapeutic strategies can be used as complementary methods to existing diagnostic approaches to manage cognitive deficits as well as clinical and physiological abnormalities of individuals in need. This book focuses on various aspects of music and its role in enhancing health and recovering from a disease. Chapters explore music as a healing method across civilizations and measure the effect of music on human physiology and functions.